2017
DOI: 10.1152/ajprenal.00096.2017
|View full text |Cite
|
Sign up to set email alerts
|

The sulfilimine cross-link of collagen IV contributes to kidney tubular basement membrane stiffness

Abstract: Basement membranes (BMs), a specialized form of extracellular matrix, underlie nearly all cell layers and provide structural support for tissues and interact with cell surface receptors to determine cell behavior. Both macromolecular composition and stiffness of the BM influence cell-BM interactions. Collagen IV is a major constituent of the BM that forms an extensively cross-linked oligomeric network. Its deficiency leads to BM mechanical instability, as observed with glomerular BM in Alport syndrome. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 39 publications
6
72
0
Order By: Relevance
“…However, it is notable that Pxdn gene inactivation by deletion of exon1 and its 5 upstream sequences leads to no apparent developmental defect in kidney, esophagus, or aorta, which is different from the defects of Col IV mutant mice [4]. A recent study using Pxdn KO mice generated by exon 9 deletion also showed no alteration of BM structure in the renal glomeruli or tubules, but reported a finding that reduced Col IV sulfilimine crosslinks reduced renal tubular BM stiffness [27]. This finding corresponds with our finding suggesting the importance of BM integrity driven by PXDN.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is notable that Pxdn gene inactivation by deletion of exon1 and its 5 upstream sequences leads to no apparent developmental defect in kidney, esophagus, or aorta, which is different from the defects of Col IV mutant mice [4]. A recent study using Pxdn KO mice generated by exon 9 deletion also showed no alteration of BM structure in the renal glomeruli or tubules, but reported a finding that reduced Col IV sulfilimine crosslinks reduced renal tubular BM stiffness [27]. This finding corresponds with our finding suggesting the importance of BM integrity driven by PXDN.…”
Section: Discussionmentioning
confidence: 99%
“…The links are formed by the matrix enzyme peroxidasin. Bhave et al recently showed that in a mouse model with reduced collagen IV sulfilimine cross‐links, a reduction in renal TBM stiffness was observed …”
Section: The Role Of the Bm In Kidney Tubulesmentioning
confidence: 98%
“…The interaction between cells and BMs is of high importance for the development of tissues, their homeostasis, and also for the response to injury . The macromolecular composition as well as the stiffness of the BM can affect the interactions between cells and the BM . Defects of BM components have been associated with kidney diseases and/or adverse renal outcome .…”
Section: The Role Of the Bm In Kidney Tubulesmentioning
confidence: 99%
“…Nonfibrillar collagen IV can also be cross‐linked, but by the sulfilimine bonds (S=N) between a methionine sulfur and a lysine nitrogen. This is an evolutionary mechanism to define mechanical properties of basement membranes .…”
Section: Extracellular Matrix Composition and Dynamicsmentioning
confidence: 99%